A capillary-induced self-assembly method under external constraint for fabrication of high-aspect-ratio and square array of optical fibers. (6th January 2023) - Feng, Kunpeng; Dang, Hong; Zhou, Weiye; Zhu, Shengqi; Hu, Yang; Sun, Xun; Cui, Jiwen; Zu, Wenlong; Jin, Zixiong; Zhang, Xuping
Abstract: High-aspect-ratio square optical fiber arrays enable massive applications from nanoscale to mesoscale, while fabrication is becoming a challenge. Here, a simple and inexpensive method is proposed based on capillary-induced self-assembly and tailored external constraints. The steady-state solution of the liquid morphology equation indicates that the interaction between optical fibers and liquid drives the array into shapes with lower free energy. Therefore, a well-designed external constraint, which affects the balance between capillarity and elastic restoration, can regulate the final arrangement of the optical fibers. Based on the dynamic analyses of the droplet-to-column transitions, liquid flow along optical fibers, and approach of optical fiber driven by liquid bridge and viscous damping, the factors influencing the capillary-induced self-assembly process are investigated, and the fabrication conditions are thus optimized. Experimental results verified the proposed method. The fabricated vector tactile sensing probe achieves a square array with aspect ratios of 135. Its displacement resolutions in three dimensions are proven better than 60 nm. Graphical abstract: Unlabelled Image Highlights: Mechanism of capillary-induced self-assembly is investigated. External constraint and critical condition is found to fabricate high-aspect-ratio and regular square array of optical fibers. Influence factors are analyzed and fabrication conditions are optimized. Micro vector tactile sense probe is fabricated and tested.